2020
DOI: 10.12669/pjms.36.5.2303
|View full text |Cite
|
Sign up to set email alerts
|

Influence of electronic nicotine delivery systems (ENDS) in comparison to conventional cigarette on color stability of dental restorative materials

Abstract: Objective: The use of Electronic Nicotine Delivery Systems (ENDS) is increasing rapidly. However, its discoloring effect on dental restorations is not known. This study aimed to evaluate the effect of ENDS aerosol when compared to conventional cigarette smoke (CS) on the color stability of dental ceramic (DC) and resin composite (RC). Methods: This research project was conducted from November 2018 to May 2019. In this study 30 discs each for DC and RC materials were fabricated to be equally divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 22 publications
(29 reference statements)
1
30
0
Order By: Relevance
“…Some of these devices are more essential, being made of standard test tubes 17) eventually connected to standard vacuum cleaners 30) . Other systems are more sophisticated, using one or more chambers made of glass 26,32) or acrylic 13,14) . In some cases, different pumps, provided of flowmeters to keep the flow constant 32) , are used to create negative and positive pressure in the chamber, reproducing the inflow and the outflow of smoke 32) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of these devices are more essential, being made of standard test tubes 17) eventually connected to standard vacuum cleaners 30) . Other systems are more sophisticated, using one or more chambers made of glass 26,32) or acrylic 13,14) . In some cases, different pumps, provided of flowmeters to keep the flow constant 32) , are used to create negative and positive pressure in the chamber, reproducing the inflow and the outflow of smoke 32) .…”
Section: Discussionmentioning
confidence: 99%
“…Other systems are more sophisticated, using one or more chambers made of glass 26,32) or acrylic 13,14) . In some cases, different pumps, provided of flowmeters to keep the flow constant 32) , are used to create negative and positive pressure in the chamber, reproducing the inflow and the outflow of smoke 32) . Beside these custom-made apparatus, one more advanced exposure system is available, the Vitrocell System.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to E-cigarettes, Vohra et al (2020) found evidence that E-cigarette aerosol exposure caused an increase in the staining F I G U R E 3 Forest plot for subgroup analysis of discoloration of resin composite from exposure to cigarette smoke/extract and E-cigarette aerosol compared with a nonexposure control. CI, confidence interval; E-cigarette, electronic cigarette; SD, standard deviation.…”
Section: Effect On Dental Ceramicmentioning
confidence: 99%
“…Four studies assessed the effect of E-cigarettes in comparison to cigarette smoke on dental staining (Dalrymple et al, 2018(Dalrymple et al, , 2021Vohra et al, 2020;Zhao et al, 2019). Data were pooled from these, and evidence found that E-cigarettes when compared with cigarette smoke cause less dental staining (MD: −9.137; 95% CI: −14.15, −4.58; I 2 : 99%; Figure 4).…”
Section: E-cigarette and Cigarette Smokementioning
confidence: 99%